2015
DOI: 10.4236/oalib.1101342
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Conformational Traits on Dairy Cattle Production and Their Longevities

Abstract: The dairy industry faces a unique challenge to constantly improve functionality of the dairy cows to meet the needs of future production and reproduction demands. The basis of improvements is selection of the best animals. The accuracy of selection can be increased by using the combined analysis of both direct information on herd life and indirect information obtained from conformation traits. Generally, conformation traits are important in dairy cattle development. These traits are used for selection of anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
12
0
4
Order By: Relevance
“…The exterior score gEBV selected in this study were mostly related to size. Body size has been associated with longevity and efficiency (Getu and Misganaw, 2015;Kern et al, 2015); however, the direction of the associations found varied, and some studies find no effect at all (Sewalem et al, 2004). Even when studies find negative associations, culling decisions may be influenced by a (regional) farmer preference for larger cows (Hansen et al, 1999;Caraviello et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The exterior score gEBV selected in this study were mostly related to size. Body size has been associated with longevity and efficiency (Getu and Misganaw, 2015;Kern et al, 2015); however, the direction of the associations found varied, and some studies find no effect at all (Sewalem et al, 2004). Even when studies find negative associations, culling decisions may be influenced by a (regional) farmer preference for larger cows (Hansen et al, 1999;Caraviello et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…From the length of CI we can make assumptions about the individual cow and herd reproductive health and about the cow's efficiency in herd (Pryce et al, 2004;Bujko et al, 2013). For analyzed cows, the average CI was 399.6 days long (from the third to fourth lactation for LB breed cows) to 407.3 days long (from the fourth to fifth lactation for HBW breed cows), furthermore, LB breed cows in all lactations had shorter CI than HBW breed cows.…”
Section: Resultsmentioning
confidence: 99%
“…In the second lactation, between calving ages of cows in the first and fourth group appeared difference of 156.6 than that for LB breed cows. Studies show that the breed of cows and cow milk productivity are the main factors that show the biggest impact on NSPC in different lactations, because of the tendency to repeat service for cows with higher milk productivity (Cummins et al, 2012;Bujko et al, 2013). The main environmental factor that affects NSPC is the heat detection system in the farm.…”
Section: →3mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering existence a different level of positive correlation between linear type traits and longevity indicators (Vacek et al 2006;Zavadilová et al 2009;Morek-Kopec and Zarnecki 2012;J. du Toit et al 2012;Kern et al 2015), a sufficient heritability level of conformation traits (Wiggans et al, 2006;de Haas et al, 2007) and the ability to score animals in the first lactation, linear type traits can be used as predictors of longevity (Vukasinovic 2002;Esteves et al, 2004); Getu and Misganaw 2015). Numerous scientific studies have proven the longevity of dairy cows as an indicator of health, animal welfare and a sustainable system of milk production (VanRaden and Wiggans 1995;Essl 1998;Sewalem et al, 2005;Zavadilová et al 2009;Du Toit et al, 2012;Olechnowicz et al, 2016;).…”
Section: Introductionmentioning
confidence: 99%